2019
DOI: 10.1111/bjh.16011
|View full text |Cite
|
Sign up to set email alerts
|

How I manage patients with follicular lymphoma

Abstract: Summary Recent advances in the treatment of follicular lymphoma (FL) have provided insight into molecular and biological influences on pathogenesis and prognosis. Additionally, numerous available treatment strategies for both newly diagnosed and relapsed disease require thoughtful consideration of patient selection to avoid the burden of overtreatment and toxicities. This review provides a broad overview on our approach to managing patients with low grade FL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Follicular lymphoma is the most common subtype of indolent B-cell lymphoma. 1,2 Patients with advanced-stage FL and a high tumor burden are generally treated with immunochemotherapy, and most of them show response to treatment. However, relapse is common in patients with FL.…”
Section: Introductionmentioning
confidence: 99%
“…Follicular lymphoma is the most common subtype of indolent B-cell lymphoma. 1,2 Patients with advanced-stage FL and a high tumor burden are generally treated with immunochemotherapy, and most of them show response to treatment. However, relapse is common in patients with FL.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome in patients with FL has improved over the last 2 decades through the introduction of anti-CD20 monoclonal antibodies, which are usually used in combination with chemotherapy. Chemotherapy-free rituximab only has been proposed as a preferable approach in low tumor burden FL, but is still a matter of debate [ 20 - 22 ]. Lockmer et al [ 23 ] indicated that an initial rituximab-only approach in patients with indolent lymphomas was associated with an increased overall survival compared with that found in other studies with first-line immunochemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…13 Cancer Center, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, China. 14 National Clinical Research Center for Hematologic Diseases, Jiangsu Institute of Hematology, The First Affiliated Hospital of Soochow University, Suzhou, China. 15 15Shengli Clinical Medical College of Fujian Medical University, Department of Hematology, Fujian Provincial Hospital, Fujian Medical University, Fuzhou, China.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…In general, the management of patients with FL1-2 depends on the disease stage and symptoms at presentation. Asymptomatic patients with low tumor burdens often approached with a watchful-waiting strategy [ 12 ], whereas symptomatic patients need to be treated, preferably with immunochemotherapy [ 13 , 14 ]. The regimen combining rituximab and the alkylating agent bendamustine (BR) represents a better therapeutic option for previously untreated patients with low-grade FL (FL1-2) than other regimens combining rituximab with cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) or with cyclophosphamide, vincristine, and prednisone (R-CVP) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%